Association between Brachyspira and irritable bowel syndrome with diarrhoea. Issue 6 (11th November 2020) - Jabbar, Karolina S; Dolan, Brendan; Eklund, Lisbeth; Wising, Catharina; Ermund, Anna; Johansson, Åsa; Törnblom, Hans; Simren, Magnus; Hansson, Gunnar C
Abstract : Objective: The incidence of IBS increases following enteric infections, suggesting a causative role for microbial imbalance. However, analyses of faecal microbiota have not demonstrated consistent alterations. Here, we used metaproteomics to investigate potential associations between mucus-resident microbiota and IBS symptoms. Design: Mucus samples were prospectively collected from sigmoid colon biopsies from patients with IBS and healthy volunteers, and their microbial protein composition analysed by mass spectrometry. Observations were verified by immunofluorescence, electron microscopy and real-time PCR, further confirmed in a second cohort, and correlated with comprehensive profiling of clinical characteristics and mucosal immune responses. Results: Metaproteomic analysis of colon mucus samples identified peptides from potentially pathogenic Brachyspira species in a subset of patients with IBS. Using multiple diagnostic methods, mucosal Brachyspira colonisation was detected in a total of 19/62 (31%) patients with IBS from two prospective cohorts, versus 0/31 healthy volunteers (p<0.001). The prevalence of Brachyspira colonisation in IBS with diarrhoea (IBS-D) was 40% in both cohorts (p=0.02 and p=0.006 vs controls). Brachyspira attachment to the colonocyte apical membrane was observed in 20% of patients with IBS and associated with accelerated oro-anal transit, mild mucosal inflammation, mast cell activation and alterations of molecular pathways linked to bacterial uptake and ion–fluid homeostasis. Metronidazole treatment paradoxically promoted Brachyspira relocation into goblet cell secretory granules—possibly representing a novel bacterial strategy to evade antibiotics. Conclusion: Mucosal Brachyspira colonisation was significantly more common in IBS and associated with distinctive clinical, histological and molecular characteristics. Our observations suggest a role for Brachyspira in the pathogenesis of IBS, particularly IBS-D.